Training report in Climate-Smart Agriculture and Climate Information Services Prioritization - Dossou-Yovo, Elliott Ronald; Tchetan, Blaise; Guindo, Jonathan; Koné, Pierre (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture, food and nutrition security, and the livelihoods of millions of people are affected by climate change. Given the scarce resources of most of the West African countries, there is a need to prioritize the technologies that need to be taken at scale to mitigate the climate change impacts. AICCRA-Mali developed a stakeholders prioritization framework to assess the locally suitable interventions in the diverse rice-based production systems in Mali. The prioritization is made in two steps. First, all interventions are evaluated by stakeholders based on their climate-smart performance indicator (ability to increase farm productivity, income, and resilience and reduce greenhouse gas emission). Second, the interventions are evaluated based on their implementation feasibility (technical feasibility, cost, gender inclusivity, demand by the market, and alignment with the social and cultural context). A training session was organized to capacitate stakeholders in the implementation of the prioritization framework for identifying locally relevant CSA and CIS interventions that can be taken to scale.